Daily hasless and uplifts at work: Perceived effects on well-being - Junça Silva, A.; Caetano, António (The happiness compass – Theories, actions and perspectives for well-being, 2013)
The affective events theory (AET) highlights the role of affective daily events at work as proximal causes of emotional reactions. Using this theory and the cognitive appraisal theory, we aim to identify the main hassles and uplifts at work and the emotional reactions they evoke, levels of intensity, and perceived effects on individuals’ well-being. By means of a qualitative and exploratory study we identified six general categories of daily uplifts and seven general categories of daily hassles. We identified a total of 276 events, of which, 160 were positive and 116 were negative. The most frequent overall category of daily uplifts was positive interpersonal interactions at work, while the most frequently identified category within daily hassles was operational hassles. Overall, our results indicate that the most frequent emotional reactions to daily uplifts were satisfaction and contentment, whereas the most common emotional reactions to daily hassles were sadness and upset. In addition, the data showed that the most intense emotional reactions to daily uplifts were linked to receiving recognition. This category also had a higher frequency of lasting emotional effects and positive perceived effects on well-being. On the other hand, emotional reactions to daily hassles were described as being more intense and having greater effects on events that threatened self-image. We also discuss promising directions for further research, as well as practical and theoretical implications related to enhancing the quality of work life.